Role of biopsy in Benign recurrent intrahepatic cholestasis: Report of two rare cases - Sankar, Raasi; Krishnasamy, Narayanasamy; Ramasamy, Akilandeswari Alagan (Annals of Pathology and Laboratory Medicine, 2020)
Benign recurrent intrahepatic cholestasis (BRIC) is an inherited self limiting cholestatic disorder. It is very rare and less common than its severe form, Progressive familial intrahepatic cholestasis (PFIC). Due to impaired canalicular biliary excretion, patients develop recurrent episodes of jaundice and intense pruritus with characteristic symptom free intervals. Most of the cases have a benign course and are managed symptomatically. Histopathological examination of liver biopsy is essential in cases of recurrent intrahepatic cholestasis to confirm the diagnosis. Here we report two cases of biopsy confirmed Benign recurrent intrahepatic cholestasis for its rarity.